2022
DOI: 10.1371/journal.pone.0269599
|View full text |Cite
|
Sign up to set email alerts
|

Association of prehospital airway management technique with survival outcomes of out-of-hospital cardiac arrest patients

Abstract: Introduction Despite numerous studies on airway management in out-of-hospital cardiac arrest (OHCA) patients, the choice of prehospital airway management technique remains controversial. Our study aimed to investigate the association between prehospital advanced airway management and survival outcomes according to a transport time interval (TTI) using nationwide OHCA registry database in Korea. Methods The inclusion criteria were patients with OHCA aged over 18 years old with a presumed cardiac etiology betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Cardiopulmonary resuscitation is very useful for saving life because by giving chest and lung compressions, the patient's circulation can return to the patient's vital organs, especially to the brain and heart itself, accompanied by simple artificial respiration so that ventilation and oxygen exchange occurs in the lungs (H. A. Chen et al, 2022;Jung et al, 2022;. The existence of cardiopulmonary resuscitation provides oxygen intake and blood circulation to body systems, especially organs that are very vital and sensitive to lack of oxygen such as the brain and heart.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiopulmonary resuscitation is very useful for saving life because by giving chest and lung compressions, the patient's circulation can return to the patient's vital organs, especially to the brain and heart itself, accompanied by simple artificial respiration so that ventilation and oxygen exchange occurs in the lungs (H. A. Chen et al, 2022;Jung et al, 2022;. The existence of cardiopulmonary resuscitation provides oxygen intake and blood circulation to body systems, especially organs that are very vital and sensitive to lack of oxygen such as the brain and heart.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of cardiopulmonary resuscitation provides oxygen intake and blood circulation to body systems, especially organs that are very vital and sensitive to lack of oxygen such as the brain and heart. Cessation of circulation (either a few seconds or even a few minutes) is an emergency condition because the supply of oxygen to the brain stops, and brain hypoxia can occur which results in the ability of the brain's coordination to move autonomic organs to be disturbed, such as heart rate and breathing movements (Borkowska et al, 2021;Jung et al, 2022;Kuo et al, 2022;. This rescue will be very useful if it is done as well as possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An observational study of 70 530 out-of-hospital cardiac arrests (OHCAs) from the nationwide database in Korea concluded that, after adjustment for confounders, in comparison with use of BMV and insertion of an SGA [adjusted odds ratio (OR), 1.07; 95% confidence interval (CI) 1.01-1.12] or tracheal intubation-adjusted (OR: 1.11, 95% CI 1.03-1.20) was associated with significantly higher survival to hospital discharge [4]. In the fully adjusted statistical model, the odds of a favourable functional outcome were significantly lower in the SGA group compared with the BMV group (adjusted OR 0.85; 95% CI 0.77-0.93) but was not significantly different when comparing tracheal intubation with BMV [adjusted OR (aOR) 0.94; 95% CI 0.80-1.08].…”
Section: Airway Management For Out-of-hospital Cardiac Arrestmentioning
confidence: 99%